Continuous aspiration prior to intracranial vascular embolectomy (CAPTIVE): a technique which improves outcomes. (16th December 2016) - McTaggart, Ryan A; Tung, Eric L; Yaghi, Shadi; Cutting, Shawna M; Hemendinger, Morgan; Gale, Heather I; Baird, Grayson L; Haas, Richard A; Jayaraman, Mahesh V
Abstract : Background: Modern stent retriever-based embolectomy for patients with emergent large vessel occlusion improves outcomes. Techniques aimed at achieving higher rates of complete recanalization would benefit patients. Objective: To evaluate the clinical impact of an embolectomy technique focused on continuous aspiration prior to intracranial vascular embolectomy (CAPTIVE). Methods: A retrospective review was performed of 95 consecutive patients with intracranial internal carotid artery or M1 segment middle cerebral artery occlusion treated with stent retriever-based thrombectomy over an 11-month period. Patients were divided into a conventional local aspiration group (traditional group) and those treated with a novel continuous aspiration technique (CAPTIVE group). We compared both early neurologic recovery (based on changes in National Institute of Health Stroke Scale (NIHSS) score), independence at 90 days (modified Rankin score 0–2), and angiographic results using the modified Thrombolysis in Cerebral Ischemia (TICI) scale including the TICI 2c category. Results: There were 56 patients in the traditional group and 39 in the CAPTIVE group. Median age and admission NIHSS scores were 78 years and 19 in the traditional group and 77 years and 19 in the CAPTIVE group. Median times from groin puncture to recanalization in the traditional and CAPTIVE groups were 31 min and 14 min, respectively (p<0.0001). While rates of TICI 2b/2c/3 recanalization were similar (81% traditional vs 100% CAPTIVE), CAPTIVE offered higher rates of TICI 2c/3 recanalization (79.5% vs 40%, p<0.001). Median discharge NIHSS score was 10 in the traditional group and 3 in the CAPTIVE group; this difference was significant. There was also an increased independence at 90 days (25% traditional vs 49% CAPTIVE). Conclusions: The CAPTIVE embolectomy technique may result in higher recanalization rates and better clinical outcomes.